Beyond Perfect Grammar: Artificial Intelligence, Writing Development, and Academic Integrity - Asrul Muarif; Muhammad Tahir; Andi Anto Patak (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2026)
The increasing use of Artificial Intelligence (AI) tools in higher education has significantly influenced students’ academic writing practices, raising concerns about writing development and academic integrity. This study explores how AI impacts students’ writing skills and academic integrity from the perspectives of English lecturers teaching academic writing courses at a state university in Indonesia. Employing a qualitative research design, data were collected through semi-structured interviews and classroom observations. Reflexive Thematic Analysis was used as the primary analytical approach, supported by metadata analysis to strengthen data interpretation. The findings indicate that AI contributes positively to surface-level writing aspects such as grammatical accuracy and text organization. However, excessive reliance on AI tools tends to reduce students’ originality, critical thinking, and engagement in the writing process. Lecturers also reported growing challenges in maintaining academic integrity, as AI-generated texts often blur the boundaries between assistance and misconduct. The absence of clear institutional policies and the limited reliability of AI detection tools further complicate the issue. This study concludes that while AI has the potential to support students’ writing development, its uncontrolled use poses serious risks to authentic learning and academic integrity. The findings highlight the importance of developing AI literacy, adopting process-oriented assessment, and establishing institutional guidelines to ensure the ethical integration of AI in academic writing instruction.